The Impact of an Educational Program on the Improvement of Football Skills among Individuals with Down Syndrome - Abu-Shihab, Esam Najeh; Al-Odaily , Ra'fat Omar (Dirasat: Educational Sciences, 2020)
This study aims at identifying the impact of a proposed educational program on the improvement of some basic skills in football among individuals with Down Syndrome. The researcher used an experimental approach with an experimental group as well as pre- and post-measurements. The study sample consisted of (20) male individuals with Down Syndrome, whose ages ranged between (18-22 years), selected with an intentional method from Aqraba Rehabilitation Center for people with disabilities. Means and standard deviations were calculated to describe the level of performance in the pre- and post-application of the study tests. T-test for related samples was calcualted to reveal the differences between performance in the pre- and post-tests for the experimental group in the study tests. The results of the study showed that there are statistically significant differences at the level (α≤0.05) between the pre- and post-measurements for learning some basic skills in football among the experimental group individuals in favor of the post-measurement among the individuals with Down syndrome. The researcher recommends using the proposed program as a means for learning some basic skills in football among the individual with Down Syndrome.